Modelling the binding of organic molecules to metal-organic frameworks - Bound, Michelle (2018)
Modelling of the fundamental interactions between small organic molecule to metal-organic frameworks (MOFs) and MOF-like structures has been carried out using a variety of computational techniques to further understand and aid in the design of MOFs for gas storage and separation applications. MOFs are an emerging class of porous crystal materials made up of organic linkers and metal nodes that are being researched for many different applications including gas storage and separations. Understanding the adsorption process is vital for the future design of better adsorbents, tailored to application. There are many useful experimental techniques currently in use but the cost and complexity for many systems is great. In this thesis, the importance of computational investigations in this area is illustrated, in particular focussing on binding that occurs between MOF surfaces and gaseous molecules. A number of computational techniques are employed in this work including ab initio electron correlation and DFT calculations, looking at binding between linker like fragments and various organic molecules and classical GCMC simulation methods, used to study the uptake and binding of small gaseous molecules at, in particular, lower pressures. The different techniques used are evaluated and compared before being utilised on a variety of structures to illustrate the significance of functionalisation within organic linkers on adsorption within MOFs. Results show the importance of a combination of computational and experimental techniques to achieve the deepest understand of binding within MOFs and, to further develop and design MOFs for adsorption applications, optimum functionalisation of linkers within MOF structures is essential.